Resolving human-elephant conflict in Luwero District, Uganda, through elephant translocation - Wambwa, Elizabeth; Manyibe, Thomas; Litoroh, Moses; Gakuya, Francis; Kanyingi, John (Pachyderm, 2001)
Since the early 1970s migration routes between Queen Elizabeth and Murchison Falls NPs have been increasingly cut off by settlement and agricultural land, and elephant living in the area have become isolated subpopulations. Capture and translocation were chosen as the management option to deal with four adult elephants (2 bulls, 2 cows) involved in crop raiding, property damage, and competition for water in the Luwero area. The animals were anaesthised darted from a helicopter, and were loaded onto trucks and transported Murchison Falls NP. Article describes procedures used in locating, anaesthetizing, loading, transporting , and safely releasing the animals. One of which was radio collared while the other three were paint marked for further monitoring. The work was undertaking by the Kenya Wildlife Service Translocation Team in conjunction with staff for the Uganda Wildlife Authority